Comprehensive analysis of biochemical compounds, chemical elements and metabolites modifications in maize plants infected with maize rayado fino virus (MRFV) - Silva de Andrade M.V. (2024)
© 2024Maize cultivation is crucial worldwide, especially in Latin America. However, diseases related to corn stunt complex have significantly impacted crops, reducing grain productivity and quality. Maize rayado fino virus (MRFV) is part of this complex, and its symptom is characterized by chlorotic dots along veins and, depending on maize genotype, there will be stunting and an impact on the corn cob development, which can lead to productivity losses. However, this intricate plant-pathogen relationship is yet not well understood. Here, we investigated the effects of MRFV transmitted by the corn leafhopper Dalbulus maidis in infected plants in their early stage of development. To show the impact of the viral infection in the maize plant, we performed biochemical and chemical analysis and nuclear magnetic resonance (NMR). The total set of analyses showed that changes in chemical and biochemical compounds, as well as in metabolites composition and activities, can be perceived in MRFV-infected maize plants when compared to healthy plants. An increase in the activity of superoxide dismutase, catalase, peroxidase, and β-glucanase was detected, whereas small changes have been identified in antioxidant activity and phenolic compounds. For chemical components, unique changes were observed, mainly the increase in the presence of some elements such as calcium (Ca), phosphorus (P), sodium (Na), and iron (Fe). We identified 20 metabolites of the amino acids, organic compounds, and carbohydrates classes in maize plants which are regulated during MRFV infection. Maize plants reacted to D. maidis herbivory by modulating both enzymatic and non-enzymatic activities, as well as chemical compounds. This research offers insights into the responses of maize against MRFV and sheds light on parameters to be used on the search of rayado fino viral disease resistance for a sustainable production.